2017
DOI: 10.4103/2303-9027.194703
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of laparoscopic ultrasonography in laparoscopic resection of insulinoma

Abstract: Insulinoma is the most common functioning islet cell tumor of the pancreas, with an annual incidence of 4 cases/1 million individuals. It is treated by surgical methods. Open surgery was once considered the standard approach for the treatment of insulinoma. However, the procedure is traumatic and requires a large incision, which does not satisfy the growing expectations of minimally invasive management of small-sized tumors. Insulinomas are usually benign solitary tumors and mostly occur sporadically, which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…However, An et al. 2 , 5 , 11 reported a high sensitivity of 86.5% for CEUS in patients with insulinomas. According to Chinese standards, four patients (33.3%) in the present study were overweight (body mass index (BMI) ≥24.0 and <28.0 kg/m 2 ) and seven patients (58.3%) were obese (BMI ≥28.0 kg/m 2 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, An et al. 2 , 5 , 11 reported a high sensitivity of 86.5% for CEUS in patients with insulinomas. According to Chinese standards, four patients (33.3%) in the present study were overweight (body mass index (BMI) ≥24.0 and <28.0 kg/m 2 ) and seven patients (58.3%) were obese (BMI ≥28.0 kg/m 2 ).…”
Section: Discussionmentioning
confidence: 98%
“…The sensitivity of ultrasonography is affected by various factors, such as the physician's expertise, patient's body weight, tumor size, and tumor location, leading to reported sensitivities of 0% to 86.5%. However, An et al 2,5,11 reported MDCT-IA, multi-detector CT during intra-arterial infusion of contrast medium.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the diagnosis of insulinoma is often delayed due to varied clinical presentations, low-specificity clinical diagnostic models, and the costly equipment of SPECT ( Dauben et al, 2019 ; Giannis et al, 2020 ). Hence, early and accurate diagnosis and treatment are crucial for a better prognosis ( Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgical resection is associated with shorter hospitalisation compared to traditional open surgical approaches; however, a disadvantage is the inability to perform manual palpation for intraoperative localisation. Laparoscopic ultrasonography can be useful and has been shown to have a sensitivity of around 90% ( 15 ). As this case demonstrates, however, the resection of small insulinomas can be challenging despite the use of pre-operative and intraoperative localisation techniques.…”
Section: Discussionmentioning
confidence: 99%